Assessment of bismuth oxide-based electrolytes for composite gas separation membranes. Issue 17 (1st December 2020) - Starykevich, M.; Jamale, A.; Marques, F.M.B.
Abstract: Oxide + salt composites can be used in CO2 and NOx separation membranes, where high oxide-ion conductivity is crucial to improve performance. Pursuing this goal, the stability of three different bismuth oxide-based electrolytes (Cu + V, Y and Yb-doped) against molten alkali carbonates (Li, Na, K) or nitrates (Na, K) was tested firing them in the 450–550 °C temperature range, and with endurance tests up to 100 h. A well-known ceria-based composite was used as reference (CGO - Ce0.9 Gd0.1 O1.95 ). Oxides and composites were studied by X-ray diffraction, scanning electron microscopy and impedance spectroscopy (in air, 140–650 °C temperature range). Bi2 Cu0.10 V0.90 O5.35 easily reacts with molten salts. Bi0.75 Y0.25 O1.5 and Bi0.75 Yb0.25 O1.5 have higher stability against molten carbonates and complete stability against molten nitrates. The Y-doped oxide stability against the molten carbonates was enhanced changing the molten salt composition (Y2 O3 additions) and using lower firing temperatures. Above all, composites based on Y or Yb-doped Bi2 O3 with molten alkali nitrates showed impressive 6× or 3× higher electrical conductivity at 290 °C, in air (4.88 × 10 −2 and 2.41 × 10 −2 S cm −1, respectively) than CGO-based composites (7.72 × 10 −3 S cm −1 ), qualifying as promising materials for NOx separation membranes. Graphical abstract: Image 1 Highlights: Bi-based ceramic electrolytes show high stability in contact with molten nitrates. Suitable dopants (oxide and/or salt) enhance the stability of Bi-based ceramics against molten alkali carbonates. Bi-based composites (ceramic + alkali nitrates) show higher conductivity than state of the art ceria-based composites. Y or Yb-doped Bi2 O3 are promising candidates for NOx separation membranes.